Historical language contact between Indo-European and Semitic in argument structure and in clause organization - (:unkn) unknown (Russian State University for the Humanities, 2018)
This paper discusses some aspects of the functional competition between nominal morphology and verbal morphology to express low transitivity in different IE languages with respect to other areally contiguous language families. In West and North IE (Celtic, Germanic, Baltic, Slavic), experience predicates often select oblique experiencers, which are also common in Finno-Ugric. In West and North IE, the inherited middle conjugation is decaying or lost altogether, replaced by structures based on the reflexive pronoun. By contrast, in South and East IE (Anatolian, Greek, Early Indo-Iranian and Tocharian), the middle inflection is still productive and represents the main strategy to encode experience predicates, in addition to denominal verb formations; in these languages, oblique experiencers are much more rare than in West and North IE. South and East IE languages have striking correspondences with Semitic, which is also poor in oblique experiencers and in impersonal constructions in its earliest varieties. In Ancient Semitic, the experiencer is regularly the subject of the clause, while low transitivity is expressed by a highly articulated verbal morphology. Accordingly, the preferred use of verbal suffixes or of oblique cases to express low transitivity-both inherited from PIE-tend to be reinforced in different IE areas by the contact with different language families where these strategies are also more or less productive. © 2018 Journal of Language Relationship. All rights reserved.
Keywords: Binyanim; Experience predicates; Indo-European; Middle conjugation; Non-canonical subject marking; Semitic